What’s Good for Women Is Good for Science: Evidence from the American Finance Association - Adams, Renée; Lowry, Michelle (The Review of Corporate Finance Studies, 2022)
Abstract Motivated by evidence that the largest gender differences in career outcomes arise within occupations, we examine a single occupation. With the support of the American Finance Association (AFA), we surveyed AFA members on the professional culture within finance. Individual experiences vary substantially, especially across men and women. Contrary to conventional narratives, differences in preferences play little role in explaining why women experience worse outcomes. Bias and discrimination have the largest effect. The consequences of noninclusiveness extend beyond the personal to the entire field. Our findings suggest that institutions potentially could do more than they recognize to improve both diversity and science. (JEL I23, J16, J24, J44, J71)